DETERMINAN MANAJEMEN LABA PADA SEKTOR INDUSTRI BARANG KONSUMSI DI INDONESIA - Andry Priharta; Siti Hamidah Rustiana; Dewi Puji Rahayu; Maryati Maryati; Nur Hadiansah (POLITEKNIK LP3I JAKARTA, 2022)
This research aims to empirically prove whether free cash flow, leverage, institutional ownership and profitability affect earnings management. The research was conducted at manufacturing companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2014-2018 period with a regression analysis of panel data fixed effects model.Â Through purposive sampling, there are 38 companies for the research and the results prove that partially, free cash flow has a significant negative effect, leverage has a significant positive effect, and profitability has a significant positive effect, while institutional ownership has a positive and insignificant effect. Simultaneously, all independent variables have a significant effect on earnings management with a determination coefficient of 96% while the remaining four percent is influenced by other factors.Keywords : Free cash flow, leverage, institutional ownership, profitability, earnings management